2017
DOI: 10.1097/bsd.0000000000000406
|View full text |Cite
|
Sign up to set email alerts
|

The Ideal Cage Position for Achieving Both Indirect Neural Decompression and Segmental Angle Restoration in Lateral Lumbar Interbody Fusion (LLIF)

Abstract: The cage position within the anterior 1/3 of disk space is better for achieving the restoration of the SA without compromising the indirect neural decompression, if the height of cage is large enough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 24 publications
2
87
0
3
Order By: Relevance
“…LLIF decompress the neural elements indirectly by increasing disc height, instead of resecting disc and bony structure which lead to stenosis. The increase of the height of foraminal area (FA) and of the cross-sectional area of the thecal sac (CSA) will lead to indirect decompression of the nerve roots and dural sac, which has been reported by previous studies (3,4).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…LLIF decompress the neural elements indirectly by increasing disc height, instead of resecting disc and bony structure which lead to stenosis. The increase of the height of foraminal area (FA) and of the cross-sectional area of the thecal sac (CSA) will lead to indirect decompression of the nerve roots and dural sac, which has been reported by previous studies (3,4).…”
Section: Introductionmentioning
confidence: 73%
“…The benefit of LLIF on SA has been reported in many studies. Park et al (4). reported greater increase in anterior disc height and SA when the cage was placed in the anterior 1/3 area than in the middle 1/3 area.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the indirect neural decompression effect of LLIF for lumbar stenosis has been addressed in previous studies [3,4,[9][10][11][12][13], the purpose of the current study was to evaluate the indirect neural decompression effect in patients with extreme lumbar spinal stenosis. The average changes in CD and CCA of grade D were 2.50 ± 1.25 mm and 16.11 ± 10.70 mm 2 , which were comparable with the effects in other grades, and indicated that the indirect decompression effect is not compromised in patients with extreme spinal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with extreme lumbar spinal stenosis are not good candidates for LLIF alone. Stand-alone LLIF is not suggested for such patients, but with concomitant posterior decompression, LLIF can achieve a satisfactory clinical outcome for extreme lumbar spinal stenosis.Although the indirect neural decompression effect of LLIF for lumbar stenosis has been addressed in previous studies[3,4,[9][10][11][12][13], the purpose of the current study was to evaluate the indirect neural decompression effect in patients with extreme lumbar spinal stenosis. The average changes in CD and CCA of grade D were 2.50 ± 1.25 mm and 16.11 ± 10.70 mm 2 , which were comparable with the effects in other grades, and indicated that the indirect decompression effect is not compromised in patients with extreme spinal stenosis.…”
mentioning
confidence: 99%